PENGARUH MEDIA E-POCKETBOOK HIV/AIDS TERHADAP PENGETAHUAN REMAJA MENGENAI PENCEGAHAN HIV/AIDS (Jurnal Kesehatan Siliwangi, 2021)
HIV/AIDS is still a global epidemic problem, including in Indonesia. The government continues to make breakthroughs and various programs in tackling the problem of HIV/AIDS where the most highlighted aspect is prevention and control efforts to achieve the Three Zero target by 2030. To achieve this target, the Ministry of Health implements a strategy to accelerate counseling, discovery, treatment and maintenance (STOP in Bahasa). The counseling aspect of the STOP strategy is the main aspect of HIV/AIDS prevention, namely to provide education in the form of health promotion to the public about HIV/AIDS. Although prevention continues to be disseminated, it cannot be denied that the percentage of people with HIV is still relatively high. Therefore, the researchers designed an alternative health promotion media in the form of an E-Pocketbook as a learning medium for HIV/AIDS prevention. The purpose of this study was to analyze the effect of HIV/AIDS E-Pocketbook media on adolescent knowledge about HIV/AIDS prevention. This research is a type of pre-experimental research with a one group pretest-posttest without control design on 85 teenagers in class X SMAN 19 Bandung in 2021. This study uses a questionnaire measuring instrument. Data analysis used univariate and bivariate with Wilcoxon Signed Test at 0.05. The results of the data analysis showed the influence of the HIV/AIDS E-Pocketbook media to increase knowledge of HIV/AIDS prevention in adolescents in class X SMAN 19 Bandung.